A framework for the rechargeable energy for multi-vehicle Travelling Salesman Problem with single repository. Issue 5 (15th April 2020) - Anitha, N.; Vijayalakshmi, C.
ABSTRACT: This paper deals with the optimisation of various resources in a network under multiple objectives such as project duration and cost criteria. In this work, the Multiple electric Vehicles are considered to be the Multiple Travelling Salesman Problem (mTSP). The main objective of this work is to reduce the overall travelling expenses and travelling space by the different Electric Vehicles. Hence with the condition that each one of the city is visited strictly once by one electric vehicle and the travelling dimensions keep on in definite boundaries. In this effort, Fuzzy Multi Objective Linear Programming is formulated to solve the multiple TSP with single repository with numerical computations.